Foraging behaviour and habitat use in the European starling, Sturnus vulgaris, in an agricultural environment - Whitehead, S; Krebs, J; Whitehead, Siân Carolyn (1994)
﻿ Recent changes in agricultural practice have reduced the diversity of habitats for a number of bird species, including the European Starling Sturnus vulgaris. I investigated the distribution of a starling population on farmland, and related this distribution to the availability of suitable habitats by studying the foraging behaviour of individual birds. I observed a preference of the overwintering flock for established pasture fields, particularly those which were closer to the central roost, which had shorter grass and which provided feeding areas further from hedges. I also demonstrated the role of leatherjacket Tipula paludosa availabilities in influencing the starlings' choice of feeding site. These prey were shown experimentally to be preferred over earthworms Lumbricus spp. which were the other main type of invertebrate prey available. I was unable to detect any systematic temporal pattern of habitat use which could have been linked to an appropriate theoretical framework (e.g. Ideal Free Distribution). I investigated the impact of starling foraging on prey availability by observing the behaviour of captive starlings allowed to forage in small enclosures. These experiments indicated that, at the level of foraging pressure expected in natural flocks, there was no significant resource depression during a single flock feeding visit to any one site. Furthermore I proposed that the extent of resource depression during the winter was insufficient to cause a shift in the birds' choice of foraging habitat over this period. The apparent lack of effects of resource depression raised the question of why starlings did not feed in the most preferred fields all the time. Further enclosure experiments investigated how an individual's foraging success might be affected by feeding with conspecifics. I found no evidence for enhancement or depression of foraging success as a result of feeding where another bird had just previously foraged, and little evidence for an effect of feeding in the presence of two other birds, despite changes in vigilance and time spent fighting. A possibly greater heterogeneity of these effects when in the natural flock situation was considered in relation to the observed flock departures. These and other effects (e.g. sampling the environment) were discussed as possible causes for the observed flock movements between fields. A final enclosure experiment investigated the impact of starling foraging on prey availability during the breeding season and demonstrated significant resource depression in a preferred field over the chick-feeding period. I then discussed starling foraging and the availability of suitable habitats in relation to the documented population decline of this species.